E.A. Goldenweiser papers - Goldenweiser, E. A. (Emanuel Alexandrovich), 1883-1953.
Correspondence, memoranda, speeches, reports, notes, congressional testimony, and other papers relating chiefly to Goldenweiser's service as director of the Division of Research and Statistics, Board of Governors of the Federal Reserve System (U.S.). Subjects include financial and economic affairs especially concerning affairs of the Board of Governors of the Federal Reserve System (U.S.). Correspondents include Dean Acheson, Louis Dembitz Brandeis, Paul H. Douglas, Marriner S. Eccles, Carter Glass, John Maynard Keynes, Charles Rist, Fred M. Vinson, and Ralph A. Young.
Economist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Dean, -- 1893-1971 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Douglas, Paul H. -- 1892-1976 -- Correspondence; Eccles, Marriner S. -- 1890-1977 -- Correspondence; Glass, Carter, -- 1858-1946 -- Correspondence; Keynes, John Maynard, -- 1883-1946 -- Correspondence; Rist, Charles, -- 1874-1955 -- Correspondence; Vinson, Fred M., -- 1890-1953 -- Correspondence; Young, Ralph A. -- 1901- -- Correspondence; Board of Governors of the Federal Reserve System (U.S.); Board of Governors of the Federal Reserve System (U.S.). -- Division of Research and Statistics; Economics; Finance, Public -- United States; United States -- Economic policy -- 20th century; Economists